OTS 44: disk and accretion at the planetary border - Joergens, Viki; Bonnefoy, M.; Liu, Y.; Bayo, A.; Wolf, S.; Chauvin, G.; Rojo, P. (Astronomy and astrophysics, 2013)
We discover that the very low-mass brown dwarf OTS 44 (M9.5, ~12 MJup) has significant accretion and a substantial disk, which demonstrates that the processes that accompany canonical star formation occur down to a central mass of a few Jupiter masses. We discover in VLT/SINFONI spectra that OTS 44 has strong, broad, and variable Pa β emission that is evidence for active accretion at the planetary border. We also detect strong Hα emission of OTS 44 in a literature spectrum and determine an Hα EW of −141 Å, which indicates active accretion. Both the Pa β and Hα emission lines have broad profiles with wings extending to velocities of about ±200 km s-1. We determine the mass accretion rate of OTS 44 based on Hα to 7.6 × 10-12 . This result shows that OTS 44 has a relatively high mass-accretion rate considering its small central mass. This mass rate is nevertheless consistent with the general decreasing trend found for stars of several solar masses down to brown dwarfs. Furthermore, we determine the properties of the disk surrounding OTS 44 through radiative transfer modeling of flux measurement from the optical to the far-IR (Herschel) by applying a Bayesian analysis. We find that OTS 44 has a highly flared disk (β > 1.2) with a mass of 9.1 , i.e. ~0.1 or 30 MEarth. We show that the ratio of the disk-to-central-mass of about 10-2 found for objects between 0.03 and 14 is also valid for OTS 44 at a mass of ~0.01 . Our observations are in line with an isolated star-like mode of the formation of brown dwarfs down to 0.01 .
Gesehen am 08.04.2021
Letter to the editor